PEMERIKSAAN KADAR GULA DARAH SEWAKTU PADA MASYARAKAT DUSUN SAMU MAMBAL KABUPATEN BADUNG - DEWI, D.A.P. RASMIKA (Buletin Udayana Mengabdi; Vol 7 No 2 (2008): Jurnal Udayana Mengabdi, 2012)
ABSTRACT The measurement of random blood sugar (BSN) for people of Banjar Samu at Desa Mekar Buana Mambal in Badung Regency, aimed for screening Diabetes Mellitus (DM) disease as effort for early detection of this disease. Otherwise the counseling of DM aimed to increase the people knowledge. The increasing people knowledge about DM was expected to change the people behaviors, so this disease can be prevented, especially at people that have high risk factors. Otherwise, in the people that has been suffered DM, we have expected the blood sugar concentration would be more controllable and the medication would give more satisfying result. The early detection of DM by this screening, have expected to degrade the risk of disease complications, improved live quality, and lengthen the age of the patients.This activities had been done on Monday, September 15th 2008 from 09.00 a.m. until finish, in Bale Banjar Samu, Desa Mekar Buana Mambal, Badung Regency. The term of this activity was counseling and free of charges BSN measurement, for people of Banjar Samu, consist both women and men. The counseling had been given by Dr. dr. I Wayan Putu Sutirta Yasa, MSi., represent the Supervisor of Clinical Immunology at Sanglah Hospital Clinical Laboratory Installation. Free of charges measurement consisted of body weight, blood pressure, and BSN from 97 people of Banjar Samu, which age range from 26 year’s until 80 year’s old. From 97 people of Banjar Samu that had been checked, we founded 3 people with the BSN concentration 293 mg/dl, 384 mg/dl, and 210 mg/dl that mean exceeding normal mark (< 200 mg/dl).